Análise e projeto de sistemas de propulsão híbridos para tratores agrícolas - Moreira, William Klaus (2022)
This Master Thesis presents the design of a series-parallel hybrid topology applied to an agricultural tractor, coupled to a seeder-fertilizer. The system is described analytically, analyzing the energy flow between the elements that compose the powertrain, and a methodology is proposed based considering individual efficiencies and the calculated fuel consumption. The adopted strategy is evaluated for different configurations and parameters, evaluating the power curves of each machine and energy source, aiming the efficienty optimization of the agricultural operation involved. Power converters are simulated in real time, along with the electrical machines, in order to evaluate the transient dynamics of the embebbed control.